Cross-sectional and prospective study of the effects of GH therapy on metabolic panel in children with GH deficiency - V. Ramistella; M. Wasniewska; S. Arasi; M. Catena; M.R. Velletri; D. Corica; S. Santucci; F. De Luca (PAGEPress Publications, 2014)
Background: Numerous studies have shown that GH, in addition to promoting linear growth, exerts a key role in many metabolic processes. However, there are only few studies aiming at evaluating the metabolic panel of children with GH deficiency (GHD). The aims of the study were: to verify the presence of metabolic alterations in GHD children in comparison with age-matched controls and to check the possible effects of two year GH therapy on the metabolic parameters in GHD. Study design: cross-sectional and prospective; one center experience Population and Methods: We enrolled 32 pediatric GHD patients (group A) and 33 sex- and age-matched healthy controls (group B). Baseline serum assays (lipid, insulin, glucose) were performed in both groups. GHD children underwent replacement therapy with GH. The same assays were repeated after 12 and 24 months of GH treatment. Results: No differences, in basal assays were found between the two groups. In group A, after initiation of GH, there was a significant increase of basal insulin and HOMA- insulin resistance (IR) index (p <0.001). In children with severe GHD (peak GH <3 ng / ml), after beginning of GH therapy a significant improvement in the lipid profile was found (p < 0.05). Conclusions: a) At the time of diagnosis GHD children had a metabolic picture that was not different from non- GHD group; b) in children with severe GHD, the metabolic profile showed a trend towards at improvement after the initiation of replacement therapy with GH, with beneficial effects in terms of total cholesterol, LDL cholesterol and cardiovascular risk indices; c) GHD patients with unfavorable metabolic profile (high BMI and hypercholestorolemia) need a monitoring of glucose metabolism by periodical evaluations of insulin and HOMA - IR.